SIMULASI: PENERAPAN SISTEM PENDUKUNG KEPUTUSAN (SPK) UNTUK TINGKAT ADAPTASI SANTRI DENGAN METODE FUZZY SUGENO - Hasanul Fahmi (Lembaga Penelitian dan Pengabdian (LPPM) STMIK Pelita Nusantara Medan, 2018)
Many santri who cannot help with the boarding school environment cause the boarding school to experience difficulties in the problems that occur in the boarding school environment which causes the santri to not survive and develop in the Islamic boarding school environment. With the help of the Decision Support System and the Sugeno fuzzy method, it can help the santri Islamic boarding school to be disapproved. The Decision Support System Simulation with the Sugeno fuzzy method can determine the level of adaptation of the santri in the Islamic boarding school so that it can help the boarding school. From the simulation results, the system has 5 criteria for adaptation of the santri and the resulting output can be approved or cannot be approved. From the simulation results with input 5 criteria, it is obtained that 24.222222222222230 cannot be approved while 21.63676767676767682 can be used.